The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1742-6596/1495/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of active layer thickness on the cut-off frequency of a-IGZO thin film transistors

Abstract: Design optimizations like channel length and gate/contact overlap length scaling are generally used for cut-off frequency (fT ) enhancement of thin film transistors (TFT). But channel length scaling leads to mobility degradation due to contact resistance (RC ). RC in TFTs is directly proportional to the transfer length (LT ), and is inversely proportional to the overlap length (LOV ). LT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These previous works offer conflicting results with some studies indicating reduced contact resistance (R C ) and shorter L T with decreasing thickness owing to reduced parasitic resistance of the bulk contact region [11], while other studies report a reduced R C with increasing thickness due to better channel morphology [21]. In our previous work [22], through TCAD based simulations, transfer length was estimated from the x-intercepts of the TLM lines by graphical method of L T extraction. It was shown that active layer thickness scaling leads to reduced L T , which can offer opportunities for overlap length scaling, leading to a lower parasitic capacitance.…”
Section: Introductionmentioning
confidence: 92%
“…These previous works offer conflicting results with some studies indicating reduced contact resistance (R C ) and shorter L T with decreasing thickness owing to reduced parasitic resistance of the bulk contact region [11], while other studies report a reduced R C with increasing thickness due to better channel morphology [21]. In our previous work [22], through TCAD based simulations, transfer length was estimated from the x-intercepts of the TLM lines by graphical method of L T extraction. It was shown that active layer thickness scaling leads to reduced L T , which can offer opportunities for overlap length scaling, leading to a lower parasitic capacitance.…”
Section: Introductionmentioning
confidence: 92%